Association between Overweight and Obesity and Functional Constipation in Children and Adolescents: Evidence from a Narrative Review - Omed Hidayat , Mabast; Asad Shkur , Dlnya; Hawla Shekha , Mohammed; Mustafa Abdulla , Zhalla; Hassan Rasul , Hardy (Hammurabi Journal of Medical Sciences, 2026)
Background: Functional constipation (FC) is marked by infrequent, hard, and painful bowel movements that are difficult to pass. It is a diagnosis of exclusion, not caused by an identifiable anatomical or medical condition. The cycle usually involves voluntary stool retention, which increases water absorption in the colon, producing harder, drier stools that are more painful to eliminate, thereby sustaining the cycle. Objectives: The goal of this narrative review is to assess the relation of overweight/obesity and functional constipation (FC) in children and adolescents. Methods: A systematic search from 2004 to 2023 included articles on “functional constipation,” “obesity,” and “children” in English in major databases. The inclusion criteria focused on studies that examined the prevalence and association of these conditions in children and adolescents, resulting in only eight eligible articles. These selected studies, including five cross-sectional observational studies, two case-control studies, and one randomized controlled trial, are crucial for evaluating the association between obesity and functional constipation in children. Results: This review examines eight studies investigating the relationship between functional constipation and overweight/obesity in children. While six studies found a significant association between the two conditions, two did not confirm this link. Notably, a systematic review highlighted a strong correlation between functional defecation disorders and excess body weight in children. The studies encompassed various designs, including observational and experimental approaches. However, some studies failed to find a significant association between obesity and constipation. Overall, the results highlight the multifactorial nature of these pathologies, which require tailored interventions to address their prevalence and differences between populations. Conclusions: The association between childhood obesity and FC is unclear due to conflicting evidence. While some studies show a significant association, others show contradictory results. Limitations such as study design and sample size contribute to this uncertainty. Future research should prioritize longitudinal studies to understand this association in children and adolescents better.